Effect of COVID-19 on the implementation of a multifaceted intervention to improve teamwork and quality for hospitalized patients: a qualitative interview study - Iva A. Terwilliger; Milisa Manojlovich; Julie K. Johnson; Mark V. Williams; Kevin J. O'Leary (BMC, 2022)
Abstract Background Healthcare organizations made major adjustments to deliver care during the COVID pandemic, yet little is known about how these adjustments shaped ongoing quality and safety improvement efforts. We aimed to understand how COVID affected four U.S. hospitals' prospective implementation efforts in an ongoing quality improvement initiative, the RE designing S yst E ms to Improve T eamwork and Quality for Hospitalized Patients (RESET) project, which implemented complementary interventions to redesign systems of care for medical patients. Methods We conducted individual semi-structured interviews with 40 healthcare professionals to determine how COVID influenced RESET implementation. We used conventional qualitative content analysis to inductively code transcripts and identify themes in MAXQDA 2020. Results We identified three overarching themes and nine sub-themes. The three themes were (1) COVID exacerbated existing problems and created new ones. (2) RESET and other quality improvement efforts were not the priority during the pandemic. (3) Fidelity of RESET implementation regressed. Conclusion COVID had a profound impact on the implementation of a multifaceted intervention to improve quality and teamwork in four hospitals. Notably, COVID led to a diversion of attention and effort away from quality improvement efforts, like RESET, and sites varied in their ability to renew efforts over time. Our findings help explain how COVID adversely affected hospitals' quality improvement efforts throughout the pandemic and support the need for research to identify elements important for fostering hospital resilience.